(Meth)acrylic resin composition, molded article using same, and method for producing (meth)acrylic resin composition

By using a ring structure catalyst composed of phosphates, alcohols and derivatives, the (methacrylic resin is solved in terms of thermal stability and ring structure formation efficiency, and the effects of low roll pollution and high thermal stability are achieved.

JP7659087B2Active Publication Date: 2025-04-08NIPPON SHOKUBAI CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023574054
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-14
Filing Date
2023-01-12
Publication Date
2025-04-08
Estimated Expiration
2043-01-12

AI Technical Summary

Technical Problem

The existing methacrylic resins have shortcomings in thermal stability and ring structure formation efficiency, especially the -roll pollution and silver stripes caused by the catalyst used, which affect the stability and yield efficiency of the resin.

Method used

A ring structure catalyst composed of phosphates, alcohols and their derivatives is used to control the content and selectivity of the catalyst, reduce roll pollution and silver stripes, while improving the thermal stability of the resin and the formation efficiency of the ring structure.

Benefits of technology

The high thermal stability and low roll pollution of methacrylic resin are achieved, which reduces silver stripes and improves production efficiency and product stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659087000001
    Figure 0007659087000001
  • Figure 0007659087000002
    Figure 0007659087000002
  • Figure 0007659087000003
    Figure 0007659087000003
Patent Text Reader

Abstract

The present invention addresses the problem of providing a (meth)acrylic resin composition which makes it possible to reduce the contamination of a roll and prevent the occurrence of silver streaks, and which has excellent stability. The present invention also addresses the problem of providing: a molded article using the (meth)acrylic resin composition; and a method for producing the (meth)acrylic resin composition. Provided is a (meth)acrylic resin composition that contains a (meth)acrylic polymer having, in a main chain thereof, a ring structure that is at least one of a lactone ring structure and a glutaric anhydride structure, the (meth)acrylic resin composition being characterized in that the content of phosphorus atoms in the (meth)acrylic resin composition is 1.0 ppm to 50 ppm inclusive and the content of a compound represented by formula (I) in the (meth)acrylic resin composition is 95 ppm or less. (I): HO―R1 [In formula (I), R1 represents an aliphatic hydrocarbon group having 13 or more carbon atoms or an aromatic hydrocarbon group having 6 or more carbon atoms.]
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a (meth)acrylic resin composition, a molded article using the same, and a method for producing the (meth)acrylic resin composition. [Background technology]

[0002] (Meth)acrylic resins are suitable for use in optical components because they have an excellent balance of various properties such as optical properties, mechanical strength, moldability, and surface hardness. However, (meth)acrylic resins generally have a low glass transition temperature (Tg) and are not excellent in heat resistance. Therefore, (meth)acrylic resins in which a ring structure such as a lactone ring structure is introduced into the main chain in order to improve the heat resistance of (meth)acrylic resins are known. As a method for producing (meth)acrylic resins having a lactone ring structure, for example, a method has been proposed in which, in a polymer having a hydroxy group and an ester group in the molecular chain, an organic phosphorus compound is used as a catalyst to form a lactone ring structure in the molecular chain by condensation ring formation through heating (Patent Documents 1 and 2). In Patent Document 1, the catalysts specifically used are methyl phosphate and phenylphosphonous acid. In Patent Document 2, the catalyst specifically used is stearyl phosphate. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2001-151814 A [Patent Document 2] JP 2017-145387 A Summary of the Invention [Problem to be solved by the invention]

[0004] Methyl phosphate and the like specifically used in Patent Document 1 had low cyclization efficiency. Therefore, in order to form a desired ratio of ring structures in the polymer, it was necessary to use a large amount of catalyst. If a large amount of catalyst was used, there was a risk that a large amount of catalyst-derived components (compounds containing phosphorus atoms) would remain in the resulting (meth)acrylic resin composition. Since phosphorus atoms are corrosive, there was concern about the stability of the (meth)acrylic resin. On the other hand, if the amount of catalyst was reduced, there was a risk of silver streaks occurring in the (meth)acrylic resin composition. In addition, when stearyl phosphate specifically used in Patent Document 2 was used as a cyclization catalyst, there was a problem that the surface of the roll used in the production of the film was easily contaminated when the resin was made into a film. If the surface of the roll was contaminated, there was a risk that the appearance of the resulting film would be impaired or production efficiency would decrease.

[0005] Regarding this problem, Patent Document 2 considers suppressing the contamination of the roll surface by controlling the content of phosphorus element and hindered phenol compound having a molecular weight of less than 300 in the resin composition, that is, by controlling the amount of phosphorus-based antioxidant having a hindered phenol moiety used (not adding excessively). However, even if the amount of phosphorus-based antioxidant having a hindered phenol moiety used is suppressed, a source of contamination of the roll surface still exists, and since stearyl phosphate is used in a specific example, it was thought that there was a limit to the suppression of the contamination of the roll surface.

[0006] The present invention has been made in view of the above-mentioned circumstances, and an object of the present invention is to provide a (meth)acrylic resin composition which can reduce roll contamination, further suppresses the occurrence of silver streaks, and has excellent stability. Another object of the present invention is to provide a molded article using the (meth)acrylic resin composition, and a method for producing the (meth)acrylic resin composition. [Means for solving the problem]

[0007] As a result of intensive investigations to solve the above-mentioned problems, the present inventors have found that the contamination is caused by adhesion of stearyl phosphate or a component derived therefrom (stearyl alcohol, etc.) used as a cyclization catalyst to the roll surface, and that when an ester obtained from phosphoric acid, phosphorous acid, hypophosphorous acid, etc. and a low or medium aliphatic alcohol (particularly an aliphatic alcohol having 3 to 12 carbon atoms) is used as a cyclization catalyst, the catalyst is stable in the cyclization step, the amount of catalyst used can be reduced, the generation of silver streaks is suppressed, and a (meth)acrylic resin composition with excellent stability can be obtained, and that when an ester obtained from phosphoric acid, phosphorous acid, hypophosphorous acid, etc. and a low or medium aliphatic alcohol is used as a cyclization catalyst, the catalyst is easily volatilized and removed in the devolatilization step, and further, the low or medium aliphatic alcohol generated by decomposition is also removed in the devolatilization step, thereby reducing roll contamination caused by the cyclization catalyst, thereby completing the present invention. That is, the present invention is defined by the following configuration requirements. [1] A (meth)acrylic resin composition comprising a (meth)acrylic polymer having at least one of a lactone ring structure and a glutaric anhydride structure in a main chain, The content of phosphorus atoms in the (meth)acrylic resin composition is 1.0 ppm or more and 50 ppm or less, A (meth)acrylic resin composition, characterized in that the content of a compound represented by the following formula (I) in the (meth)acrylic resin composition is 95 ppm or less: [ka] [In formula (I), R 1 represents an aliphatic hydrocarbon group having 13 or more carbon atoms, or an aromatic hydrocarbon group having 6 or more carbon atoms. [2] The (meth)acrylic resin composition according to [1], wherein the content of the compound represented by the following formula (II) in the (meth)acrylic resin composition is 95 ppm or less: [ka] [In formula (II), R 2represents an aliphatic hydrocarbon group having 3 to 12 carbon atoms. [3] The (meth)acrylic resin composition according to [1] or [2], wherein the content of ring structural units in the (meth)acrylic polymer having a ring structure is from 5% by mass to 70% by mass. [4] The (meth)acrylic resin composition according to any one of [1] to [3], wherein the content of the (meth)acrylic polymer having a ring structure in the (meth)acrylic resin composition is 50 mass % or more. [5] The (meth)acrylic resin composition according to any one of [1] to [4], which has a glass transition temperature of 120° C. or higher. [6] The (meth)acrylic resin composition according to any one of [1] to [5], which does not contain a hindered phenol compound. [7] The (meth)acrylic resin composition according to any one of [1] to [6], which does not contain an organophosphorus compound having a hindered phenol moiety. [8] A molded article comprising the (meth)acrylic resin composition according to any one of [1] to [7]. [9] The molded article according to [8], which is in the form of a sheet, film or lens.

[10] A method for producing a (meth)acrylic resin composition, comprising a cyclization step of carrying out at least one of the following cyclization reactions (i) and (ii) in a (meth)acrylic polymer to form a ring structure in a main chain of the (meth)acrylic polymer, (i) A cyclization reaction between a hydroxy group and an ester group or a carboxyl group to form a lactone ring structure. (ii) A cyclization reaction between a carboxyl group and an ester group or another carboxyl group to form a glutaric anhydride structure. In the cyclization reaction, phosphate C 3-12 Alkyl ester, phosphorous acid C 3-12 Alkyl esters and hypophosphorous acid C 3-12 A method for producing a (meth)acrylic resin composition, characterized in that at least one selected from the group consisting of alkyl esters is used as a catalyst.

[11] The catalyst used in the cyclization reaction is phosphoric acid C 3-7Alkyl ester, phosphorous acid C 3-7 Alkyl esters and hypophosphorous acid C 3-7 The method for producing a (meth)acrylic resin composition according to

[10] , wherein the (meth)acrylic resin is at least one selected from the group consisting of alkyl esters.

[12] The method for producing a (meth)acrylic resin composition according to

[10] or

[11] , wherein the catalyst used in the cyclization reaction is at least one selected from the group consisting of butyl phosphate, butyl phosphite, and butyl hypophosphite.

[13] The method for producing a (meth)acrylic resin composition according to any one of

[10] to

[12] , wherein the amount of the catalyst used is 1000 ppm or less based on the total amount of monomer components constituting the (meth)acrylic polymer.

[14] The method for producing a (meth)acrylic resin composition according to any one of

[10] to

[13] , wherein the catalyst has a decomposition temperature of 160° C. or higher.

[15] The method for producing a (meth)acrylic resin composition according to any one of

[10] to

[14] , further comprising a polymerization step of polymerizing a (meth)acrylic monomer to form the (meth)acrylic polymer.

[16] The method for producing a (meth)acrylic resin composition according to

[15] , wherein a total content ratio of structural units derived from the (meth)acrylic monomer in all structural units of the (meth)acrylic polymer is 50 mass% or more.

[17] The method for producing a (meth)acrylic resin composition according to

[15] or

[16] , wherein the (meth)acrylic monomer comprises an alkyl α-(1-hydroxyalkyl)acrylate, and the total content of structural units derived from the alkyl α-(1-hydroxyalkyl)acrylate in all structural units of the (meth)acrylic polymer is 5 mass% or more.

[18] An additive is added in one or more steps selected from the polymerization step, the cyclization step, and a step subsequent to the cyclization step; The method for producing a (meth)acrylic resin composition according to any one of

[15] to

[17] , wherein the additive does not contain a hindered phenol compound or an organophosphorus compound having a hindered phenol moiety. Effect of the Invention

[0008] According to the present invention, it is possible to provide a (meth)acrylic resin composition which can reduce roll contamination, inhibits the occurrence of silver streaks, and has excellent stability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] 1. (Meth)acrylic resin composition The (meth)acrylic resin composition of the present invention is characterized in that it contains a (meth)acrylic polymer having at least one of a lactone ring structure and a glutaric anhydride ring structure in the main chain, the phosphorus atom content in the composition is 1.0 ppm or more and 50 ppm or less, and the content of a compound represented by the following formula (I) in the composition is 95 ppm or less. Since the (meth)acrylic resin composition of the present invention has the above-mentioned constituent requirements, it can reduce roll contamination, and furthermore, the occurrence of silver streaks is suppressed and it has excellent stability.

[0010] [ka] [In formula (I), R 1 represents an aliphatic hydrocarbon group having 13 or more carbon atoms, or an aromatic hydrocarbon group having 6 or more carbon atoms.

[0011] In the present invention, unless otherwise specified, the term "ppm" refers to a value calculated by mass conversion (for example, 10,000 ppm corresponds to 1 mass %). 3-12 " means "having 3 or more and 12 or less carbon atoms."

[0012] 1.1 (Meth)acrylic polymers The (meth)acrylic polymer refers to a polymer having (meth)acrylic acid, a (meth)acrylic acid ester, or a derivative thereof (hereinafter, these may be collectively referred to as a (meth)acrylic monomer) as a monomer unit (i.e., a constituent unit). Note that "(meth)acrylic acid" is a term that includes both acrylic acid and methacrylic acid.

[0013] Examples of the (meth)acrylic acid ester include alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, n-hexyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; aralkyl (meth)acrylates such as benzyl (meth)acrylate (preferably methacrylic acid C 2-20 aralkyl); esters of (meth)acrylic acid and hydroxycyclic saturated hydrocarbons (preferably hydroxycyclic saturated hydrocarbons having 5 to 20 carbon atoms), such as cyclohexyl (meth)acrylate and dicyclopentanyl (meth)acrylate, etc. The (meth)acrylic acid ester is preferably a methacrylic acid ester, more preferably an alkyl methacrylate, and even more preferably a C methacrylic acid ester. 1-10 alkyl, and even more preferably methacrylic acid C 1-7 alkyl, more preferably methacrylic acid C 1-4 Alkyl, particularly preferably methacrylic acid C 1-2 It is an alkyl.

[0014] Examples of the (meth)acrylic acid ester derivatives include derivatives having a hydroxy group introduced therein, for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2,3,4,5,6-pentahydroxyhexyl (meth)acrylate, and 2,3,4,5-tetrahydroxypentyl (meth)acrylate; and α-(1-hydroxyalkyl)alkyl acrylates.

[0015] The hydroxyalkyl (meth)acrylate may be, for example, hydroxyalkyl (meth)acrylate C 1-20 Alkyl is preferred, and (meth)acrylic acid hydroxy C 1-15 Alkyl is more preferred, and (meth)acrylic acid hydroxy C 1-10 Alkyl is more preferred, and (meth)acrylic acid hydroxy C 1-5 Alkyl is even more preferred.

[0016] α-(1-hydroxyalkyl)alkyl acrylates include α-(1-hydroxyC 1-20 Alkyl)acrylic acid C 1-20 Alkyl is preferred, α-(1-hydroxyC 1-20 Alkyl)acrylic acid C 1-20 Alkyl includes α-(hydroxymethyl)acrylic acid C such as methyl α-(hydroxymethyl)acrylate, ethyl α-(hydroxymethyl)acrylate, isopropyl α-(hydroxymethyl)acrylate, n-butyl α-(hydroxymethyl)acrylate, and t-butyl α-(hydroxymethyl)acrylate. 1-20 Alkyl; α-(1-hydroxyethyl) methyl acrylate, etc. 2-20 Alkyl)acrylic acid C 1-20 Alkyl and the like are included.

[0017] As for (meth)acrylic acid ester derivatives, β-C such as methyl crotonate 1-10 Alkyl acrylic acid C 1-10 Also included are alkyl; halogen-introduced derivatives such as chloromethyl (meth)acrylate and 2-chloroethyl (meth)acrylate; and ether bond-introduced derivatives such as dicyclopentanyloxyethyl (meth)acrylate.

[0018] The (meth)acrylic acid ester derivative is preferably a derivative having a hydroxy group introduced therein, more preferably an α-(1-hydroxyalkyl)alkyl acrylate, and even more preferably an α-(1-hydroxyC 1-20 Alkyl)acrylic acid C 1-20alkyl, and even more preferably α-(hydroxymethyl)acrylic acid C 1-20 It is an alkyl.

[0019] The (meth)acrylic acid derivatives include compounds obtained by hydrolyzing the ester bond of the above-mentioned methacrylic acid ester derivatives, for example, crotonic acid, α-(hydroxymethyl)acrylic acid, 2-(1-hydroxyethyl)acrylic acid and other α-hydroxyalkylacrylic acids.

[0020] The (meth)acrylic monomers that the (meth)acrylic polymer has as monomer units may be a single type or a combination of two or more types. Of the (meth)acrylic monomers, it is preferable to include (meth)acrylic acid or a (meth)acrylic acid ester as an essential unit, and it is more preferable to include a (meth)acrylic acid ester (particularly a methacrylic acid ester) as an essential unit. The content ratio of the essential unit in the (meth)acrylic polymer is, for example, 30% by mass or more, preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 65% ​​by mass or more, even more preferably 70% by mass or more, particularly preferably 75% by mass or more, and for example, 100% by mass or less, preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less. In addition, when the (meth)acrylic polymer has a unit derived from a (meth)acrylic monomer that has become a different unit through a cyclization reaction or the like described below, the ratio of the (meth)acrylic monomer units in the content ratio does not include the unit derived from the (meth)acrylic monomer that has become the different unit.

[0021] The (meth)acrylic polymer may have a structural unit introduced by copolymerizing the (meth)acrylic monomer with another monomer. Such other monomer is not particularly limited as long as it is a compound having a polymerizable double bond, and examples thereof include styrene monomers such as styrene, vinyl toluene, α-methylstyrene, α-hydroxymethylstyrene, and α-hydroxyethylstyrene; nitrogen-containing heterocyclic vinyl compounds such as N-vinylpyrrolidone and N-vinylcarbazole; vinyl nitriles such as acrylonitrile and methacrylonitrile; vinyl alcohols such as methallyl alcohol and allyl alcohol; olefins such as ethylene, propylene, and 4-methyl-1-pentene; carboxyl group-containing ethylenic monofunctional monomers such as maleic acid, fumaric acid, crotonic acid, itaconic acid, citraconic acid, maleic acid monomethyl ester, maleic acid monobutyl ester, itaconic acid monomethyl ester, and itaconic acid monobutyl ester; vinyl acetate; 2-hydroxymethyl-1-butene; and methyl vinyl ketone. As the other monomer, a styrene-based monomer, a nitrogen-containing heterocyclic vinyl compound, and a carboxyl group-containing ethylenic monofunctional monomer are preferred, a styrene-based monomer and a carboxyl group-containing ethylenic monofunctional monomer are more preferred, and a styrene-based monomer is even more preferred. These other monomers (structural units) may be present in only one type or in two or more types. The other monomers (structural units) are, for example, 0% by mass or more, preferably 1% by mass or more, and, for example, 30% by mass or less, preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less in the (meth)acrylic polymer.

[0022] The total content ratio of the structural units derived from the (meth)acrylic monomer in the total structural units of the (meth)acrylic polymer (i.e., the (meth)acrylic acid unit, the (meth)acrylic acid ester unit, and the structural units derived from these derivatives) is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and even more preferably 75% by mass or more, from the viewpoint of the transparency of the molded product. There is no particular upper limit, and it may be 100% by mass. In addition, for a (meth)acrylic polymer having a unit derived from a (meth)acrylic monomer that has become a different unit by a cyclization reaction described later (i.e., a (meth)acrylic polymer having a ring structure), the total content ratio of the structural units derived from the (meth)acrylic monomer in the total structural units of the (meth)acrylic polymer having a ring structure is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 60% by mass or more, even more preferably 70% by mass or more, particularly preferably 75% by mass or more, and preferably 99% by mass or less, more preferably 95% by mass or less, even more preferably 90% by mass or less, and even more preferably 85% by mass or less.

[0023] The total content ratio of structural units derived from hydroxyl group-introduced derivatives of (meth)acrylic acid esters (preferably α-(1-hydroxyalkyl)alkyl acrylates) in all structural units of the (meth)acrylic polymer is preferably 1% by mass or more, more preferably 5% by mass or more, even more preferably 8% by mass or more, even more preferably 10% by mass or more, and preferably 70% by mass or less, more preferably 50% by mass or less, and even more preferably 30% by mass or less. In addition, for (meth)acrylic polymers having units derived from (meth)acrylic monomers that have become different units by cyclization reaction described later (i.e., (meth)acrylic polymers having a ring structure), the total content ratio of structural units derived from hydroxyl group-introduced derivatives of (meth)acrylic acid esters in all structural units of the (meth)acrylic polymer having a ring structure may be 0% by mass, preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 5% by mass or less.

[0024] A (meth)acrylic polymer having at least one of a lactone ring structure and a glutaric anhydride structure in the main chain can be formed, for example, by carrying out a cyclization reaction described later in a (meth)acrylic polymer having a hydroxy group, an ester group, and / or a carboxyl group.

[0025] The lactone ring structure is preferably a 4- to 8-membered ring because it is easy to form the lactone ring structure, more preferably a 5- or 6-membered ring because the ring structure has excellent stability, and even more preferably a 6-membered ring. An example of a 6-membered lactone ring structure is the structure shown in the following formula (1).

[0026] [ka]

[0027] In the above formula (1), R 1a , R 2a and R 3a are each independently a hydrogen atom or an organic residue having 1 to 20 carbon atoms, and the organic residue may contain an oxygen atom. Examples of the organic residue in formula (1) include hydrocarbon groups having 1 to 20 carbon atoms, which may have a substituent. Examples of the hydrocarbon group include saturated or unsaturated linear, branched, or cyclic aliphatic hydrocarbon groups and aromatic hydrocarbon groups. Examples of the aliphatic hydrocarbon group include alkyl groups having 1 to 20 carbon atoms, such as methyl, ethyl, n-propyl, and isopropyl groups (preferably alkyl groups having 1 to 10 carbon atoms, more preferably alkyl groups having 1 to 6 carbon atoms); alkenyl groups having 2 to 20 carbon atoms, such as ethenyl and propenyl groups (preferably alkenyl groups having 2 to 10 carbon atoms, more preferably alkenyl groups having 2 to 6 carbon atoms); cycloalkyl groups having 3 to 20 carbon atoms, such as cyclopentyl and cyclohexyl groups (preferably cycloalkyl groups having 4 to 12 carbon atoms, more preferably cycloalkyl groups having 5 to 8 carbon atoms); and the like. Examples of aromatic hydrocarbon groups include aryl groups having 6 to 20 carbon atoms, such as a phenyl group, a tolyl group, a xylyl group, a naphthyl group, and a biphenyl group (preferably an aryl group having 6 to 14 carbon atoms, more preferably an aryl group having 6 to 10 carbon atoms); aralkyl groups having 7 to 20 carbon atoms, such as a benzyl group and a phenylethyl group (preferably an aralkyl group having 7 to 15 carbon atoms, more preferably an aralkyl group having 7 to 11 carbon atoms); and the like. These hydrocarbon groups may contain an oxygen atom or a halogen atom, and specifically, one or more of the hydrogen atoms of the hydrocarbon group may be substituted with at least one group selected from a hydroxyl group, a carboxyl group, an ether group, and an ester group.

[0028] In the lactone ring structure represented by formula (1), R 1a , R 2a are each independently preferably a hydrogen atom or an alkyl group having 1 to 20 carbon atoms, more preferably a hydrogen atom or a methyl group; 3a is preferably a hydrogen atom or a methyl group, and more preferably a methyl group.

[0029] The (meth)acrylic polymer may have only one type of lactone ring structure, or may have two or more types.

[0030] When the (meth)acrylic polymer has a lactone ring structure in the main chain, the content of the lactone ring structure in the polymer is, for example, 1 mass% or more, preferably 5 mass% or more, and more preferably 10 mass% or more, and for example, 70 mass% or less, preferably 50 mass% or less, and more preferably 30 mass% or less.

[0031] The content ratio of the lactone ring structure in the (meth)acrylic polymer can be calculated from the polymerization amount of the monomers involved in the lactone cyclization (hydroxy group-containing (meth)acrylic monomer A and (meth)acrylic monomer B in the case of the cyclization reaction (i) described below) and the lactone cyclization rate according to the following formula. Content of lactone ring structure (mass%) = Z1 × Z2 × M R / M m (wherein, Z1 is the mass content of structural units derived from raw material monomers involved in lactone cyclization (hydroxy group-containing (meth)acrylic monomer A and (meth)acrylic monomer B in the case of the cyclization reaction (i) described below) in the polymer before lactone cyclization, and M R is the formula weight of the resulting lactone ring structural unit (meaning the total formula weight of the lactone ring-forming elements and the groups other than the main chain bonded to the lactone ring), and M m is the molecular weight (total) of the raw material monomers involved in the lactone cyclization (hydroxy group-containing (meth)acrylic monomer A and (meth)acrylic monomer B in the case of the cyclization reaction (i) described below), and Z2 is the lactone cyclization rate.

[0032] The content of the lactone ring structure in the (meth)acrylic polymer can be determined by a known method, for example, nuclear magnetic resonance ( 1 The molecular weight can be evaluated by 1 H-NMR (H-NMR) and / or infrared spectroscopy (IR).

[0033] An example of the glutaric anhydride structure is the structure shown in the following formula (2).

[0034] [ka]

[0035] In the above formula (2), R 4a , R 5a are each independently a hydrogen atom or an alkyl group having 1 to 8 carbon atoms. In the formula (2), the alkyl group having 1 to 8 carbon atoms is preferably a linear or branched alkyl group, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, or a tert-butyl group.

[0036] In the glutaric anhydride structure represented by formula (2), R 4a , R 5a are preferably, independently of one another, a hydrogen atom or an alkyl group having 1 to 4 carbon atoms, and more preferably a hydrogen atom or a methyl group.

[0037] The (meth)acrylic polymer may have only one type of glutaric anhydride structure, or may have two or more types.

[0038] When the (meth)acrylic polymer has a glutaric anhydride structure in the main chain, the content of the glutaric anhydride structure in the polymer is, for example, 1 mass% or more, preferably 5 mass% or more, and more preferably 10 mass% or more, and for example, 70 mass% or less, preferably 50 mass% or less, and more preferably 30 mass% or less.

[0039] The content of the glutaric anhydride structure in the (meth)acrylic polymer can be determined, for example, by the method described in JP-A-2006-131689.

[0040] The content of the ring structure unit in the (meth)acrylic polymer is preferably 5% by mass or more, more preferably 8% by mass or more, even more preferably 10% by mass or more, preferably 70% by mass or less, more preferably 50% by mass or less, even more preferably 45% by mass or less, and even more preferably 30% by mass or less. By having the content of the ring structure unit within the above range, a (meth)acrylic resin composition having excellent heat resistance and mechanical strength can be obtained. The ring structure unit in the content of the ring structure unit means a unit having a ring structure in the main chain of the (meth)acrylic polymer.

[0041] From the viewpoint of suppressing foaming during molding, the cyclization rate in the (meth)acrylic polymer is preferably 95.0% by mass or more, more preferably 95.5% by mass or more, even more preferably 96.0% by mass or more, and even more preferably 96.5% by mass or more. There is no particular upper limit, and it may be 100% by mass.

[0042] The cyclization rate can be determined, for example, based on the mass loss that occurs when all hydroxyl groups from the polymer composition obtained by polymerization are dealcoholized or dehydrated as alcohol or water, from 150°C before the mass loss begins in dynamic TG measurement to 300°C before the decomposition of the polymer begins. That is, the mass loss rate between 150°C and 300°C is measured in dynamic TG measurement of a polymer having a ring structure, and the measured mass loss rate obtained is designated as (X). On the other hand, the theoretical mass loss rate when it is assumed that all hydroxyl groups contained in the polymer composition are involved in ring formation and dealcoholized or dehydrated from the composition of the polymer (i.e., the mass loss rate calculated assuming that 100% dealcoholization or dehydration occurs in the composition) is designated as (Y). More specifically, the theoretical mass loss rate (Y) can be calculated from the molar ratio of raw material monomers having a structure (hydroxyl group) involved in the dealcoholization or dehydration reaction in the polymer, i.e., the content of the raw material monomer in the polymer composition. These values ​​(X, Y) are substituted into the formula: 1-(actual mass reduction rate (X) / theoretical mass reduction rate (Y)) to obtain the value, and the value is expressed as a percentage to obtain the cyclization rate (de-alcoholization or dehydration reaction rate).

[0043] The total content of the structural units derived from (meth)acrylic monomers (preferably units derived from (meth)acrylic acid esters) and the ring structural units in all the structural units of the (meth)acrylic polymer is preferably 90% by mass or more, more preferably 93% by mass or more, and even more preferably 95% by mass or more, which makes it easy to improve the transparency and heat resistance of the (meth)acrylic polymer.

[0044] The (meth)acrylic polymer may have at least one of a lactone ring structure and a glutaric anhydride structure as a ring structure. From the viewpoint of improving the heat resistance and optical properties of the (meth)acrylic resin composition, it is more preferable that the (meth)acrylic polymer has a lactone ring structure.

[0045] The weight average molecular weight (Mw) of the (meth)acrylic polymer is, for example, 80,000 or more, preferably 100,000 or more, more preferably 105,000 or more, and further preferably 110,000 or more, and is, for example, 300,000 or less, preferably 250,000 or less, and more preferably 200,000 or less. By having the weight average molecular weight of the (meth)acrylic polymer within the above range, it is possible to obtain a (meth)acrylic resin composition that has good fluidity during molding while maintaining the necessary strength as a resin.

[0046] The molecular weight distribution of the (meth)acrylic polymer (Mw / Mn; Mw represents the weight average molecular weight of the (meth)acrylic polymer, and Mn represents the number average molecular weight of the (meth)acrylic polymer) is, for example, 3.5 or less, preferably 3.0 or less, and more preferably 2.5 or less, and for example, 1.1 or more, preferably 1.2 or more, and more preferably 2.0 or more.

[0047] The content of the (meth)acrylic polymer having a ring structure in the (meth)acrylic resin composition is, for example, 50% by mass or more, preferably 70% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. The upper limit of the content of the (meth)acrylic polymer having a ring structure in the (meth)acrylic resin composition is less than 100% by mass.

[0048] 1.2 Phosphorus atom The (meth)acrylic resin composition of the present invention contains a phosphorus atom. The phosphorus atom is preferably derived from a catalyst used in the cyclization reaction of the (meth)acrylic polymer.

[0049] The content of phosphorus atoms in the (meth)acrylic resin composition is 1.0 ppm or more and 50 ppm or less, preferably 1.5 ppm or more and 45 ppm or less, more preferably 2.0 ppm or more and 40 ppm or less, and even more preferably 20 ppm or more and 34 ppm or less. By having the content of phosphorus atoms within the above range, the cyclization rate can be increased and the content ratio of the ring structure unit possessed by the (meth)acrylic polymer can be set within an appropriate range, so that a (meth)acrylic resin composition having excellent heat resistance and excellent mechanical strength can be obtained. In addition, by having the content of phosphorus atoms of 50 ppm or less, the occurrence of silver streaks can be suppressed and a (meth)acrylic resin composition having excellent stability can be obtained. Specifically, if the content of phosphorus atoms is 50 ppm or less, the number of corrosive phosphorus atoms is sufficiently small, so that the stability is excellent. The content of phosphorus atoms is specified by two significant digits.

[0050] 1.3 Compounds of formula (I) The (meth)acrylic resin composition of the present invention may contain a compound represented by the following formula (I), but it is preferable that it does not contain as much as possible. Specifically, the content of the compound represented by formula (I) in the (meth)acrylic resin composition is 95 ppm or less, preferably 90 ppm or less, more preferably 80 ppm or less, even more preferably 60 ppm or less, and most preferably 0 ppm (i.e., not detected by the method described in the Examples). When the content of the compound represented by formula (I) is within the above range, the adhesion between the (meth)acrylic resin composition and the roll during molding is improved, and the occurrence of roll contamination can be suppressed. The identification and content of the compound represented by formula (I) can be determined by the method described in the Examples described later. In addition, the identification is performed by rounding off the first decimal place when expressed in ppm.

[0051] [ka] [In formula (I), R 1 represents an aliphatic hydrocarbon group having 13 or more carbon atoms, or an aromatic hydrocarbon group having 6 or more carbon atoms.

[0052] R in formula (I) 1 The aliphatic hydrocarbon group represented by the formula (I) may be saturated or unsaturated and may be linear or cyclic. R 1 Examples of the aliphatic hydrocarbon group having 13 or more carbon atoms represented by the formula (I) include alkyl groups having 13 or more carbon atoms, such as tridecyl group, tetradecyl group, pentadecyl group, hexadecyl group, heptadecyl group, octadecyl group, nonadecyl group, and icosyl group; alkenyl groups having 13 or more carbon atoms, such as tridecenyl group, tetradecenyl group, pentadecenyl group, hexadecenyl group, octadecenyl group, and octadecadienyl group; cycloalkyl groups having 13 or more carbon atoms, such as cyclotridecyl group, cyclotetradecyl group, cyclopentadecyl group, cyclohexadecyl group, cycloheptadecyl group, and cyclooctadecyl group; and the like. R 1 Examples of aromatic hydrocarbon groups having 6 or more carbon atoms represented by the formula (I) include aryl groups having 6 or more carbon atoms, such as a phenyl group, a tolyl group, a xylyl group, a naphthyl group, and a biphenyl group; and aralkyl groups having 7 or more carbon atoms, such as a benzyl group and a phenylethyl group.

[0053] 1.4 Compounds represented by formula (II) The (meth)acrylic resin composition of the present invention may contain a compound represented by the following formula (II), but preferably does not contain it. Specifically, the content of the compound represented by formula (II) in the (meth)acrylic resin composition is 95 ppm or less, preferably 90 ppm or less, more preferably 80 ppm or less, even more preferably 60 ppm or less, and most preferably 0 ppm (i.e., not detected by the method described in the Examples). By having the content of the compound represented by formula (II) within the above range, roll contamination can be further reduced, and further the occurrence of silver streaks can be further suppressed, and a (meth)acrylic resin composition with excellent stability can be obtained. The identification and content of the compound represented by formula (II) can be determined in the same manner as the compound represented by formula (I). In addition, the identification is performed by rounding off the first decimal place when expressed in ppm.

[0054] [ka] [In formula (II), R 2 represents an aliphatic hydrocarbon group having 3 to 12 carbon atoms.

[0055] R in formula (II) 2 The aliphatic hydrocarbon group represented by the formula (I) may be saturated or unsaturated and may be linear or cyclic. R 2 Examples of the aliphatic hydrocarbon group having 3 to 12 carbon atoms, represented by the formula (I), include alkyl groups having 3 to 12 carbon atoms, such as n-propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, hexyl, heptyl, and octyl groups; alkenyl groups having 3 to 12 carbon atoms, such as propenyl, butenyl, pentenyl, hexenyl, heptenyl, and octenyl groups; and cycloalkyl groups having 3 to 12 carbon atoms, such as cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, and cyclooctyl groups. R 2As the alkyl group, an aliphatic hydrocarbon group having 3 to 10 carbon atoms is preferable, an aliphatic hydrocarbon group having 3 to 8 carbon atoms is more preferable, and an aliphatic hydrocarbon group having 3 to 7 carbon atoms is even more preferable.

[0056] 1.5 Other alcohol The (meth)acrylic resin composition of the present invention may contain alcohols (referred to as other alcohols) other than the compounds represented by formula (I) and formula (II). In particular, when the other alcohols are low molecular weight alcohols such as methanol and ethanol, they are volatilized and removed by heating during molding, and do not cause roll contamination. However, the content of other alcohols is preferably as low as possible, for example, 1000 ppm or less, preferably 500 ppm or less, more preferably 300 ppm or less, and may be 0 ppm.

[0057] 1.6 Other ingredients The (meth)acrylic resin composition of the present invention may contain other components as necessary in addition to the (meth)acrylic polymer having a ring structure and phosphorus atoms described above.

[0058] The (meth)acrylic resin composition of the present invention may contain, as the other components, for example, a (meth)acrylic polymer having no ring structure or a polymer other than a (meth)acrylic polymer. Examples of polymers other than (meth)acrylic polymers include olefin polymers such as polyethylene, polypropylene, ethylene-propylene polymers, and poly(4-methyl-1-pentene); halogen-containing polymers such as vinyl chloride and chlorinated vinyl resins; styrene polymers such as polystyrene, styrene-methyl methacrylate copolymer, styrene-acrylonitrile copolymer, and acrylonitrile-butadiene-styrene copolymer; polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate; polyamides such as nylon 6, nylon 66, and nylon 610; polyacetal; polycarbonate; polyphenylene oxide; polyphenylene sulfide; polyether ether ketone; polysulfone; polyethersulfone; polyoxybenzene; polyamide imide; cycloolefin polymers; cellulose derivatives; polybutadiene rubber, and rubbery polymers such as ABS resins and ASA resins blended with (meth)acrylic rubber. In the (meth)acrylic resin composition, the content of the polymer other than the (meth)acrylic polymer having a ring structure is preferably 100 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and may be 0 parts by mass, relative to 100 parts by mass of the (meth)acrylic polymer having a ring structure.

[0059] The (meth)acrylic resin composition of the present invention may contain various additives within the range that does not impair the effects of the present invention. Examples of additives include ultraviolet absorbers; phenolic antioxidants (e.g., hydroquinone, 2,6-di-t-butyl-p-cresol, tocopherol, 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene, etc.); phosphorus-based antioxidants (e.g., triphenyl phosphite, tris(2,4-di-t-butylphenyl)phosphite, etc.); sulfur-based antioxidants (e.g., 2-mercaptobenzimidazole, dilauryl 3,3'-thiodipropionate, etc.); Examples of the additives include antioxidants such as ethylhexyl phosphate, ...

[0060] The ultraviolet absorbing agent may be a benzophenone-based compound, a salicylate-based compound, a benzoate-based compound, a triazole-based compound, or a triazine-based compound, and may be any known ultraviolet absorbing agent. The benzophenone-based compound may be 2,4-dihydroxybenzophenone, 4-n-octyloxy-2-hydroxybenzophenone, or 2,2'-dihydroxy-4,4'-dimethoxybenzophenone. The salicylate-based compound may be pt-butylphenyl salicylate. The benzoate-based compound may be 2,4-di-t-butylphenyl-3',5'-di-t-butyl-4'-hydroxybenzoate. Examples of triazole compounds include 2,2'-methylenebis[4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazol-2-yl)phenol], 2-(3,5-di-tert-butyl-2-hydroxyphenyl)-5-chlorobenzotriazole, 2-(2H-benzotriazol-2-yl)-p-cresol, 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylethyl)phenol, 2-benzotriazol-2-yl-4,6-di-tert-butylphenol, 2-[5-chloro(2H)-benzotriazol-2-yl]-4-methyl-6-t-butylphenol, 2-(2H-benzotriazol-2-yl)-4,6-di-t-butylphenol, and 2-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol. Examples of triazine compounds include 2-[4,6-bis(biphenyl-4-yl)-1,3,6-triad-2-yl]-5-[(2-ethylhexyl)oxy]phenol, 2-mono(hydroxyphenyl)-1,3,5-triazine compounds, 2,4-bis(hydroxyphenyl)-1,3,5-triazine compounds, and 2,4,6-tris(hydroxyphenyl)-1,3,5-triazine compounds.Examples of commercially available ultraviolet absorbents include triazine-based ultraviolet absorbents TINUVIN (registered trademark) 1577, TINUVIN (registered trademark) 460, TINUVIN (registered trademark) 477 (manufactured by BASF Japan Ltd.), Adeka STAB (registered trademark) LA-F70 (manufactured by ADEKA Corporation), and triazole-based ultraviolet absorbent Adeka STAB (registered trademark) LA-31 (manufactured by ADEKA Corporation). Only one type of ultraviolet absorbent may be used, or two or more types may be used in combination.

[0061] On the other hand, in order to more effectively suppress roll contamination, it is preferable that the (meth)acrylic resin composition of the present invention does not contain a hindered phenol compound and / or a compound that is a source of the hindered phenol compound. This is because the hindered phenol compound causes roll contamination. Examples of the hindered phenol compound include hindered phenol-based antioxidants such as 2,6-di-t-butyl-p-cresol and 1,3,5-trimethyl-2,4,6-tris(3,5-di-t-butyl-4-hydroxybenzyl)benzene. Examples of compounds that are sources of the hindered phenol compound include organic phosphorus compounds having a hindered phenol moiety, and specifically, phosphorus-based antioxidants having a hindered phenol moiety such as tris(2,4-di-t-butylphenyl)phosphite. The hindered phenol compound is a phenol compound having at least one tertiary alkyl group such as a sterically bulky substituent, and a phenol compound having at least one tertiary alkyl group is preferable.

[0062] 1.7 Characteristics The (meth)acrylic resin composition of the present invention has a phosphorus atom content of 1.0 ppm or more and 50 ppm or less, a compound represented by the above formula (I) content of 95 ppm or less, and preferably a compound represented by the above formula (II) content of 95 ppm or less, thereby making it possible to reduce roll contamination, and furthermore to suppress the occurrence of silver streaks and provide excellent stability.

[0063] The weight average molecular weight (Mw) of the (meth)acrylic resin composition is, for example, 50,000 or more, preferably 80,000 or more, more preferably 100,000 or more, even more preferably 115,000 or more, and even more preferably 120,000 or more, and is, for example, 300,000 or less, preferably 250,000 or less, and more preferably 200,000 or less. By having the weight average molecular weight of the (meth)acrylic resin composition within the above range, it is possible to obtain a (meth)acrylic resin composition that has good fluidity during molding while maintaining the necessary strength as a resin.

[0064] The number average molecular weight (Mn) of the (meth)acrylic resin composition is, for example, 30,000 or more, preferably 35,000 or more, more preferably 40,000 or more, and is, for example, 250,000 or less, preferably 200,000 or less, more preferably 150,000 or less. By having the number average molecular weight of the (meth)acrylic resin composition within the above range, it is possible to obtain a (meth)acrylic resin composition that has good fluidity during molding while maintaining the necessary strength as a resin.

[0065] The molecular weight distribution (Mw / Mn; Mw represents the weight average molecular weight of the (meth)acrylic resin composition, and Mn represents the number average molecular weight of the (meth)acrylic resin composition) of the (meth)acrylic resin composition is, for example, 3.5 or less, preferably 3.0 or less, and more preferably 2.5 or less, and there is no particular lower limit, and it may be, for example, 1.1 or more.

[0066] The (meth)acrylic resin composition preferably has a glass transition temperature of 110° C. or higher. By having a glass transition temperature of 110° C. or higher, the heat resistance of the resin composition is enhanced. The (meth)acrylic resin composition may have a plurality of glass transition temperatures of 110° C. or higher. The glass transition temperature of the (meth)acrylic resin composition is more preferably 120° C. or higher, and even more preferably 123° C. or higher. From the viewpoint of improving processability during molding, the glass transition temperature of the (meth)acrylic resin composition is preferably less than 300° C., more preferably 200° C. or lower, and even more preferably 180° C. or lower.

[0067] The (meth)acrylic resin composition has a content of the compound represented by formula (I) of 95 ppm or less, and therefore has good adhesion.

[0068] The (meth)acrylic resin composition has good adhesion, and thus prevents roll contamination during molding. If roll contamination occurs during molding, the appearance (smoothness) of the molded product may be impaired, and production efficiency may decrease due to the need to stop the production line to remove the contamination from the roll surface.

[0069] 2. Method for producing (meth)acrylic resin composition The method for producing a (meth)acrylic resin composition of the present invention is characterized in that it comprises a cyclization step of carrying out a cyclization reaction in a (meth)acrylic polymer to form at least one ring structure selected from a lactone ring structure and a glutaric anhydride structure in a main chain of the (meth)acrylic polymer, and uses a specific cyclization catalyst as a catalyst for the cyclization reaction. The method for producing the (meth)acrylic resin composition of the present invention preferably includes a polymerization step of forming the (meth)acrylic polymer by polymerizing a (meth)acrylic monomer.

[0070] 2.1 (Meth)acrylic monomers The (meth)acrylic monomer is a polymerization component, and examples of the (meth)acrylic monomer include the same monomers as the (meth)acrylic monomers explained above, and preferred embodiments thereof are also the same.

[0071] Specifically, the (meth)acrylic monomer used in the polymerization may be a single one or a combination of two or more kinds. The (meth)acrylic monomer used in the polymerization preferably contains at least (meth)acrylic acid or a (meth)acrylic acid ester, and more preferably contains at least a (meth)acrylic acid ester. The (meth)acrylic monomer used in the polymerization preferably contains a (meth)acrylic acid ester derivative in addition to (meth)acrylic acid and / or a (meth)acrylic acid ester. In particular, the (meth)acrylic monomer used in the polymerization preferably contains a (meth)acrylic acid ester and a hydroxyl group-introduced derivative of a (meth)acrylic acid ester. From the viewpoint of transparency of the molded product, the ratio of the total amount of the (meth)acrylic monomer to the total amount of the monomer components used in the polymerization is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and even more preferably 75% by mass or more, and there is no particular upper limit, and it may be 100% by mass. The content of (meth)acrylic acid and / or (meth)acrylic acid ester in the (meth)acrylic monomer used for polymerization is, for example, 30% by mass or more, preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 65% ​​by mass or more, even more preferably 70% by mass or more, particularly preferably 75% by mass or more, and, for example, 100% by mass or less, preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less. The content of (meth)acrylic acid ester derivative (preferably α-(1-hydroxyalkyl) alkyl acrylate) relative to the total amount of monomer components used for polymerization is, for example, 1% by mass or more, preferably 5% by mass or more, more preferably 8% by mass or more, and even more preferably 10% by mass or more, and, for example, 70% by mass or less, preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less.

[0072] The monomer component that is the polymerization component may contain other monomers other than the (meth)acrylic monomer. Examples of the other monomers include the same monomers as those described above, and the preferred embodiments thereof are also the same.

[0073] The other monomers used in the polymerization may be one type only, or may be two or more types. The ratio of the total amount of the other monomers to the total amount of the monomer components is, for example, 0 mass% or more, preferably 1 mass% or more, and for example, 30 mass% or less, preferably 20 mass% or less, more preferably 10 mass% or less.

[0074] 2.2 Polymerization initiator In the polymerization reaction using a (meth)acrylic monomer, a polymerization initiator may be used as necessary.

[0075] Examples of the polymerization initiator include azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, dimethyl-2,2'-azobis(2-methylpropionate), and 4,4'-azobis(4-cyanopentanoic acid); persulfates such as potassium persulfate; and organic peroxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, di-t-butyl peroxide, lauroyl peroxide, benzoyl peroxide, t-butylperoxyisopropylcarbonate, t-amylperoxy-2-ethylhexanoate, t-amylperoxyoctoate, t-amylperoxyisononanoate, t-amylperoxyisopropylcarbonate, and t-amylperoxy2-ethylhexylcarbonate. These may be used alone or in combination of two or more. Among these, it is preferable to use an organic peroxide having a strong hydrogen abstracting power.

[0076] The amount of the polymerization initiator used is, for example, 500 ppm or more, preferably 1000 ppm or more, more preferably 1500 ppm or more, based on the total amount of the monomer components, from the viewpoint of increasing the polymerization rate and reducing the amount of remaining unreacted monomer components. The amount of the polymerization initiator used is, for example, 2 mass % or less, preferably 1 mass % or less, more preferably 0.5 mass % or less, based on the total amount of the monomer components.

[0077] In order to promote the decomposition of the polymerization initiator, a suitable amount of a decomposer for the polymerization initiator, such as a reducing agent such as sodium hydrogen sulfite or a transition metal salt such as ferrous sulfate, may be added to the reaction system.

[0078] 2.3 Chain transfer agents In order to adjust the weight average molecular weight of the (meth)acrylic polymer, a chain transfer agent may be added to the reaction system. By adding a chain transfer agent to the reaction system, the (meth)acrylic polymer can be made to have a low molecular weight. Examples of the chain transfer agent include organic thiol compounds; halogen compounds such as carbon tetrachloride, carbon tetrabromide, methylene chloride, bromoform, and bromotrichloroethane; and unsaturated hydrocarbon compounds such as α-methylstyrene dimer, α-terpinene, γ-terpinene, dipentene, and terpinolene. These chain transfer agents may be used alone or in combination of two or more. Among these, organic thiol compounds are preferred because they can suppress a decrease in conversion rate.

[0079] The organic thiol compound includes a monofunctional thiol compound and a polyfunctional thiol compound. Examples of the monofunctional thiol compound include monofunctional thiol compounds having aromatic rings such as thiophenol, 2-mercaptobenzothiazole, 2-mercaptobenzimidazole, 2-mercaptobenzoxazole, 3-mercapto-1,2,4-triazole, and octyl thioglycolate; and aliphatic monofunctional thiol compounds having no aromatic rings. Examples of the monofunctional thiol compound of the aliphatic system include monofunctional thiol compounds having heteroatoms between carbon atoms of aliphatic hydrocarbon groups such as octyl 2-mercaptopropionate, octyl 3-mercaptopropionate, 2-ethylhexyl mercaptopropionate, and 2-mercaptoethyl octanoate; and alkyl thiol compounds having no heteroatoms between carbon atoms of aliphatic hydrocarbon groups such as butanethiol, octanethiol, 1-dodecanethiol (also called n-dodecyl mercaptan), octadecanethiol, and cyclohexyl mercaptan. Examples of the heteroatom include an oxygen atom and a nitrogen atom. Examples of the polyfunctional thiol compound include polyfunctional thiol compounds having an aromatic ring, such as 1,4-dimethylmercaptobenzene and 1,3,5-triazine-2,4,6-trithiol; and aliphatic polyfunctional thiol compounds not having an aromatic ring, such as 1,8-dimercapto-3,6-dioxaoctane, ethylene glycol bisthioglycolate, trimethylolpropane tristhioglycolate, trimethylolpropane tristhiopropionate, trimethylolpropane tristhiobutanate, pentaerythritol tetrakis thioglycolate, pentaerythritol tetrakis thiopropionate, pentaerythritol tetrakis (4-mercaptobutanate), pentaerythritol tetrakis (6-mercaptohexanate), and dipentaerythritol hexakis (3-mercaptopropionate).

[0080] As the organic thiol compound, a monofunctional thiol compound is preferable, an aliphatic monofunctional thiol compound is more preferable, and an alkyl thiol compound is further preferable.

[0081] The amount of the chain transfer agent used is, for example, 200 ppm or more, preferably 400 ppm or more, and more preferably 500 ppm or more, and for example, 5 mass% or less, preferably 1 mass% or less, and more preferably 0.5 mass% or less, based on the total amount of the monomer components.

[0082] The ratio of the amount of chain transfer agent to the polymerization initiator used (amount of chain transfer agent used / amount of polymerization initiator used; mass ratio) is preferably 0.10 or more, more preferably 0.15 or more, even more preferably 0.20 or more, and is preferably 2.0 or less, more preferably 1.5 or less, even more preferably 1.0 or less. By having the ratio of the amount of chain transfer agent to the polymerization initiator used within the above range, the polymerization rate can be kept appropriate and the molecular weight distribution can be narrowed.

[0083] 2.4 Polymerization reaction (polymerization process) The polymerization method for the (meth)acrylic monomer may be batch polymerization or continuous polymerization. When a chain transfer agent is used, batch polymerization is preferred since it is possible to reduce the amount of unreacted chain transfer agent remaining. The polymerization of the (meth)acrylic monomer may be any of bulk polymerization, solution polymerization, emulsion polymerization, and suspension polymerization, but solution polymerization is preferred from the viewpoints of high safety and low risk of contamination with foreign matter.

[0084] Examples of solvents that can be used in solution polymerization include aromatic hydrocarbon solvents such as toluene, xylene, and ethylbenzene; ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ether solvents such as tetrahydrofuran, dioxane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, and anisole; ester solvents such as ethyl acetate, butyl acetate, propylene glycol monomethyl ether acetate, and 3-methoxybutyl acetate; cellosolve solvents such as methyl cellosolve, ethyl cellosolve, and butyl cellosolve; alcohol solvents such as methanol, ethanol, isopropanol, and n-butanol; nitrile solvents such as acetonitrile, propionitrile, butyronitrile, and benzonitrile; halogen solvents such as chloroform and dichloromethane; and dimethyl sulfoxide. As the polymerization solvent, aromatic hydrocarbon solvents and ketone solvents are preferred, more preferably aromatic hydrocarbon solvents, and particularly preferably toluene. These polymerization solvents may be used alone or in combination of two or more.

[0085] The total concentration of monomers (monomer components) in the polymerization reaction liquid is, for example, 5% by mass or more, preferably 10% by mass or more, more preferably 30% by mass or more, and for example, 90% by mass or less, preferably 80% by mass or less, more preferably 70% by mass or less. The amount of solvent used in the polymerization reaction is not particularly limited as long as the total concentration of monomers in the polymerization reaction liquid is within the above range.

[0086] The method of adding the monomer and the solvent used if necessary is not particularly limited. As the method of addition, the total amount may be initially charged, or a certain amount may be initially charged and the remainder may be added to the reaction system all at once or continuously during the polymerization reaction. The continuation may be continuous or may be intermittent such as divided addition, but it is preferable that the addition is continuous or intermittent with an interval of 10 minutes or less, and it is more preferable that the addition is continuous. In addition, the method of adding the polymerization initiator and the chain transfer agent used as necessary is not particularly limited. As the method of addition, the total amount may be initially charged, a certain amount may be initially charged and the remainder may be added to the reaction system all at once or continuously during the polymerization reaction, or the total amount may be introduced into the reaction system by addition. The continuation may be continuous or intermittent such as divided addition, but it is preferable that the continuation is continuous or intermittent with an interval of 10 minutes or less, and more preferable that the continuation is continuous. In addition, since the polymerization initiator can narrow the molecular weight distribution of the obtained (meth)acrylic polymer, it is preferable that the total amount is continuously added to the reaction system during the polymerization reaction, or a certain amount is initially charged and the remainder is continuously added to the reaction system during the polymerization reaction.

[0087] The atmosphere in which the (meth)acrylic monomer is polymerized is not particularly limited, but from the viewpoint of increasing the efficiency of the polymerization reaction, an inert gas such as nitrogen gas is preferable.

[0088] The polymerization temperature when polymerizing the (meth)acrylic monomer is, for example, 40°C or higher, preferably 60°C or higher, more preferably 80°C or higher. When a polymerization initiator is used, it is preferably set to a 10-hour half-life temperature or higher of the polymerization initiator used. The 10-hour half-life temperature means a temperature at which the half-life of the polymerization initiator is 10 hours. The polymerization temperature is, for example, 180°C or lower, preferably 150°C or lower, more preferably 120°C or lower. When a solvent is used, it is preferably set to a reflux temperature of the solvent used or lower.

[0089] The polymerization time for polymerizing the (meth)acrylic monomer is not particularly limited and may be appropriately set depending on the progress of the polymerization reaction, but is usually about 2 to 8 hours.

[0090] After adding all the monomers, and optionally the polymerization initiator, the chain transfer agent, and the solvent, maturation may be performed as necessary. The conversion rate of the monomers is further improved by maturation. In the maturation step, it is preferable to continue stirring at an appropriate temperature, for example, about the polymerization temperature ±30°C (preferably at the polymerization temperature or above). The maturation time is, for example, 0 hours or more and 10 hours or less, preferably 1 hour or more and 5 hours or less.

[0091] The monomer conversion at the end of the reaction is, for example, 80% or more, preferably 85% or more, and more preferably 88% or more.

[0092] The total content ratio of the structural units derived from the (meth)acrylic monomer in all structural units of the (meth)acrylic polymer obtained by polymerization reaction is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, and even more preferably 75% by mass or more, from the viewpoint of transparency of the molded product. There is no particular upper limit, and it may be 100% by mass. In addition, the total content ratio of the structural units derived from the (meth)acrylic acid ester derivative (preferably α-(1-hydroxyalkyl) alkyl acrylate) in all structural units of the (meth)acrylic polymer obtained by polymerization reaction is preferably 5% by mass or more, more preferably 8% by mass or more, even more preferably 10% by mass or more, and for example, 70% by mass or less, preferably 50% by mass or less, more preferably 30% by mass or less, and even more preferably 20% by mass or less.

[0093] 2.5 Cyclization Catalyst In the present invention, phosphoric acid C is used as the cyclization catalyst. 3-12 Alkyl ester, phosphorous acid C 3-12 Alkyl esters and hypophosphorous acid C 3-12By using at least one selected from the group consisting of alkyl esters, the cyclization reaction can be carried out efficiently, and a decrease in the adhesion of the resulting (meth)acrylic resin composition can be suppressed.

[0094] Phosphate C 3-12 Examples of alkyl esters include monopropyl phosphate, dipropyl phosphate, tripropyl phosphate, monoisopropyl phosphate, diisopropyl phosphate, triisopropyl phosphate, monobutyl phosphate, dibutyl phosphate, tributyl phosphate, mono-tert-butyl phosphate, di-tert-butyl phosphate, tri-tert-butyl phosphate, monopentyl phosphate, dipentyl phosphate, tripentyl phosphate, monohexyl phosphate, dihexyl phosphate, trihexyl phosphate, monoheptyl phosphate, diheptyl phosphate, triheptyl phosphate, monooctyl phosphate, dioctyl phosphate, trioctyl phosphate, and the like. 3-12 As an alkyl ester, phosphoric acid C 3-10 Alkyl esters are preferred, and phosphoric acid C 3-8 Alkyl esters are more preferred, with phosphoric acid C 3-7 Alkyl esters are more preferred. Phosphate C 3-8 Alkyl esters are phosphoric acid C 3-8 Linear alkyl esters are preferred, and phosphoric acid C 3-8 Mono linear alkyl ester, phosphoric acid C 3-8 Dilinear alkyl esters are more preferred. Phosphate C 3-7 Alkyl esters are phosphoric acid C 3-7 Linear alkyl esters are preferred, and phosphoric acid C 3-7 Mono linear alkyl ester, phosphoric acid C 3-7 Dilinear alkyl esters are more preferred. Phosphate C 3-12 As the alkyl ester, monobutyl phosphate and dibutyl phosphate are particularly preferred.

[0095] Phosphorous Acid C 3-12Examples of alkyl esters include monopropyl phosphite, dipropyl phosphite, tripropyl phosphite, monoisopropyl phosphite, diisopropyl phosphite, triisopropyl phosphite, monobutyl phosphite, dibutyl phosphite, tributyl phosphite, mono-tert-butyl phosphite, di-tert-butyl phosphite, tri-tert-butyl phosphite, monopentyl phosphite, dipentyl phosphite, tripentyl phosphite, monohexyl phosphite, dihexyl phosphite, trihexyl phosphite, monoheptyl phosphite, diheptyl phosphite, triheptyl phosphite, monooctyl phosphite, dioctyl phosphite, trioctyl phosphite, and the like. Phosphite C 3-12 As for alkyl esters, phosphorous acid C 3-10 Alkyl esters are preferred, and phosphorous acid C 3-8 Alkyl esters are more preferred, and phosphorous acid C 3-7 Alkyl esters are more preferred. Phosphorous acid C 3-8 Alkyl esters are phosphorous acid C 3-8 Linear alkyl esters are more preferred, and phosphorous acid C 3-8 Mono linear alkyl ester, phosphorous acid C 3-8 Dilinear alkyl esters are even more preferred. Phosphorous acid C 3-7 Alkyl esters are phosphorous acid C 3-7 Linear alkyl esters are preferred, and phosphatic acid C 3-7 Mono linear alkyl ester, phosphorous acid C 3-7 Dilinear alkyl esters are more preferred. Phosphorous acid C 3-12 As the alkyl ester, monobutyl phosphite and dibutyl phosphite are particularly preferred.

[0096] Hypophosphorous Acid C 3-12Examples of alkyl esters include monopropyl hypophosphite, dipropyl hypophosphite, tripropyl hypophosphite, monoisopropyl hypophosphite, diisopropyl hypophosphite, triisopropyl hypophosphite, monobutyl hypophosphite, dibutyl hypophosphite, tributyl hypophosphite, mono-tert-butyl hypophosphite, di-tert-butyl hypophosphite, tri-tert-butyl hypophosphite, monopentyl hypophosphite, dipentyl hypophosphite, tripentyl hypophosphite, monohexyl hypophosphite, dihexyl hypophosphite, trihexyl hypophosphite, monoheptyl hypophosphite, diheptyl hypophosphite, triheptyl hypophosphite, monooctyl hypophosphite, dioctyl hypophosphite, trioctyl hypophosphite, and the like. 3-12 As for alkyl esters, hypophosphite C 3-10 Alkyl esters are preferred, and hypophosphorous acid C 3-8 Alkyl esters are more preferred, and hypophosphorous acid C 3-7 Alkyl esters are more preferred. 3-8 Alkyl esters are hypophosphite C 3-8 Linear alkyl esters are more preferred, and hypophosphorous acid C 3-8 Mono linear alkyl ester, hypophosphorous acid C 3-8 Dilinear alkyl esters are even more preferred. 3-7 Alkyl esters are hypophosphite C 3-7 Linear alkyl esters are more preferred, and hypophosphorous acid C 3-7 Mono linear alkyl ester, hypophosphorous acid C 3-7 Dilinear alkyl esters are even more preferred. 3-12 As the alkyl ester, monobutyl hypophosphite and dibutyl hypophosphite are particularly preferred.

[0097] The cyclization catalyst may be used alone or in combination of two or more. When two or more types are used in combination, one of them may be stearyl phosphate. This is because one of the ideas of the present invention is to reduce the proportion of stearyl phosphate in the total amount of the cyclization catalyst compared to the conventional method.

[0098] As a cyclization catalyst, phosphoric acid C is preferred because of its high catalytic activity. 3-12 Alkyl esters are preferred.

[0099] The decomposition temperature of the cyclization catalyst is preferably 160° C. or higher, more preferably 180° C. or higher, and further preferably 200° C. or higher, and there is no particular upper limit, and it may be, for example, 300° C. or lower. For example, the decomposition temperature of butyl phosphate is 220° C., and the decomposition temperature of octyl phosphate is 247° C.

[0100] 2.6 Cyclization reaction (cyclization step) The (meth)acrylic polymer after the polymerization reaction is heated in the presence of the cyclization catalyst to cause dehydration condensation or dealcoholization condensation, thereby forming a (meth)acrylic polymer having a ring structure, which is at least one of a lactone ring structure and a glutaric anhydride structure, in the main chain.

[0101] Specifically, at least one of the following cyclization reactions (i) and (ii) is carried out on the (meth)acrylic polymer formed in the polymerization step. (i) A cyclization reaction between a hydroxy group and an ester group or a carboxyl group to form a lactone ring structure. (ii) A cyclization reaction between a carboxyl group and an ester group or another carboxyl group to form a glutaric anhydride structure.

[0102] In the case of the cyclization reaction (i) above, for example, first, in the polymerization reaction, a hydroxy group-containing (meth)acrylic monomer A such as an α-(1-hydroxyalkyl) alkyl acrylate is homopolymerized, or the hydroxy group-containing (meth)acrylic monomer A is copolymerized with a (meth)acrylic monomer B such as (meth)acrylic acid or a (meth)acrylic acid ester, to introduce a hydroxy group and an ester group or a carboxyl group into the molecular chain of the (meth)acrylic polymer. Then, in the cyclization reaction, a lactone ring structure can be formed by causing dealcoholization or dehydration cyclocondensation between the hydroxy group and the ester group or the carboxyl group. In the cyclization reaction of (i), the hydroxyl-containing (meth)acrylic monomer A may be the hydroxyl-containing derivative of the above-mentioned (meth)acrylic acid ester, and the preferred embodiments thereof are the same. The (meth)acrylic monomer B may be the above-mentioned (meth)acrylic acid or (meth)acrylic acid ester, and the preferred embodiments thereof are the same.

[0103] In the case of the cyclization reaction (ii) above, for example, first, in the polymerization reaction, (meth)acrylic acid is homopolymerized to introduce a carboxyl group into the molecular chain of the (meth)acrylic polymer, or a (meth)acrylic monomer B such as (meth)acrylic acid or a (meth)acrylic acid ester is polymerized (preferably copolymerized) to introduce a carboxyl group and an ester group into the molecular chain of the (meth)acrylic polymer. Then, in the cyclization reaction, a glutaric anhydride structure can be formed by causing dehydration cyclocondensation between two carboxyl groups or by causing dealcoholization between a carboxyl group and an ester group. As the (meth)acrylic monomer B in the cyclization reaction of (ii), the above-mentioned (meth)acrylic acid and (meth)acrylic acid esters can be mentioned, and the preferred embodiments thereof are also the same.

[0104] In addition, when the (meth)acrylic polymer has a double bond moiety, an ester group, a carboxyl group, or an acid anhydride group, a hydroxy group, an ester group, or a carboxyl group that will later react in the cyclization reaction may be introduced into the (meth)acrylic polymer prior to the cyclization reaction by, for example, an addition reaction of a hydroxy group to the double bond moiety, hydrolysis of the ester group, or an esterification reaction of a carboxyl group or an acid anhydride group.

[0105] In the cyclization reaction, it is sufficient that at least a portion of the hydroxyl groups, ester groups, and / or carboxyl groups of the (meth)acrylic polymer reacts, and the reaction is carried out so that the content ratio of the ring structure unit and the cyclization rate in the (meth)acrylic polymer are within the ranges described above.

[0106] The cyclization reaction may be carried out in the presence of a solvent. Examples of solvents that can be used in the cyclization reaction include the same types of solvents that can be used in the above-mentioned polymerization reaction, and preferred embodiments are also the same. When the polymerization reaction is carried out by solution polymerization, the solvent used in the solution polymerization may be removed once and then a new solvent may be added, or the solvent used in the solution polymerization may be subsequently used as the solvent in the cyclization reaction. However, from the viewpoint of production efficiency, it is preferable to subsequently use the solvent used in the solution polymerization as the solvent in the cyclization reaction.

[0107] The concentration of the (meth)acrylic polymer in the cyclization reaction solution is, for example, 5% by mass or more, preferably 10% by mass or more, more preferably 30% by mass or more, and is, for example, 90% by mass or less, preferably 80% by mass or less, more preferably 70% by mass or less. The amount of the solvent used in the cyclization reaction is not particularly limited as long as the concentration of the (meth)acrylic polymer in the cyclization reaction solution is within the above range.

[0108] The amount of the cyclization catalyst used is, for example, preferably 100 ppm or more and 1000 ppm or less, more preferably 110 ppm or more, even more preferably 120 ppm or more, still more preferably 150 ppm or more, and more preferably 900 ppm or less, even more preferably 800 ppm or less, and still more preferably 700 ppm or less, relative to the total amount of the monomer components constituting the (meth)acrylic polymer. By using an amount of the cyclization catalyst within the above range, it is possible to increase the cyclization rate, form ring structural units in the (meth)acrylic polymer at a desired ratio, and obtain a (meth)acrylic resin composition that is excellent in stability while suppressing the occurrence of silver streaks.

[0109] The method of adding the cyclization catalyst during the cyclization reaction may be such that the entire amount is initially charged, or a certain amount is initially charged and the remainder is added to the reaction system all at once or continuously during the cyclization reaction, or the entire amount may be introduced into the reaction system by addition. The continuation may be continuous or may be intermittent, such as divided addition, but is preferably continuous or intermittent at intervals of 10 minutes or less, and more preferably continuous.

[0110] The reaction temperature of the cyclization reaction is, for example, 50° C. to 300° C., and preferably 70° C. to 150° C. The reaction time of the cyclization reaction is, for example, about 5 minutes to 6 hours, and preferably 30 minutes to 3 hours. According to the cyclization catalyst of the present invention, the cyclization reaction can be efficiently carried out, and therefore even if the reaction time is less than 3 hours, the cyclization rate is high and cyclization can be achieved in which the content of the ring structure unit in the (meth)acrylic polymer falls within the above-mentioned range.

[0111] The cyclization reaction is preferably carried out in a reaction vessel in which a polymerization reaction is carried out, and further proceeded in an autoclave, a shell-and-tube heat exchanger, or the like.

[0112] After the cyclization step, it is preferable to carry out a post-treatment including a devolatilization step. The devolatilization step is a process for removing volatile matters such as the solvent and residual monomers, and the alcohol by-produced by the cyclization reaction. 3-12 Alkyl ester, phosphorous acid C 3-12 Alkyl esters and hypophosphorous acid C 3-12 If at least one selected from the group consisting of alkyl esters is used, it is easily removed by volatilization in the volatilization step. Furthermore, by carrying out the volatilization step under heating conditions, the cyclization catalyst is decomposed to generate alcohol, and it is preferable that the alcohol is also removed.

[0113] If the devolatilization is insufficient, a large amount of volatile matter remains in the (meth)acrylic resin composition, which causes foaming during molding, resulting in molding defects. In addition, when an alkyl phosphate, alkyl phosphite, or alkyl hypophosphite having 13 or more carbon atoms is used as a cyclization catalyst, the higher alcohol (alcohol having 13 or more carbon atoms) generated by decomposition of these compounds is difficult to volatilize and remains in the (meth)acrylic resin composition, thereby reducing the adhesion of the (meth)acrylic resin composition.

[0114] The apparatus used for devolatilization is not particularly limited, but for example, an autoclave, a kettle-type reactor, an apparatus consisting of a heat exchanger and a devolatilization tank, an extruder with a vent, etc. can be used, and a dryer may also be used.

[0115] When a vented extruder is used for devolatilization, the extruder preferably has a cylinder and a screw provided in the cylinder, and is provided with a heating means. The cylinder is preferably provided with one or more vents, and the vent is more preferably provided at least downstream of the raw material input section with respect to the transport direction in the extruder, and may also be provided upstream of the raw material input section. Devolatilization proceeds in the process of transferring the polymer fed into the extruder from the upstream side to the downstream side of the extruder while being kneaded with the screw. A die is preferably provided downstream of the extruder, and the polymer can be molded into a predetermined shape by discharging it from the die. For example, pellets can be produced by cutting the rod-shaped polymer into small pieces. In addition, a polymer filter is preferably provided in the die section of the extruder.

[0116] The devolatilization temperature is preferably in the range of 150° C. to 350° C., and more preferably in the range of 200° C. to 300° C. If the devolatilization temperature is lower than 150° C., there is a problem that devolatilization is insufficient and a large amount of volatile matter remains, and if it is higher than 350° C., there is a problem that coloring and decomposition occur, which is not preferable. The degree of reduced pressure during the devolatilization treatment is preferably 13.3 hPa or more (for example, about 13.3 hPa to 800 hPa).

[0117] The additive may be added in one or more steps selected from the polymerization step, the cyclization step, and a step subsequent to the cyclization step, provided that the additive does not preferably contain the hindered phenol compound and / or a compound that is a source of the hindered phenol compound.

[0118] 3. Molded body The (meth)acrylic resin composition can be molded into various forms and used as various products or parts. The shape of the molded product may be appropriately set depending on the application, and may be, for example, a plate, a granule, a powder, a lump, a particle aggregate, a sphere, an elliptical sphere, a lens, a cube, a column, a rod, a cone, a cylinder, a needle, a fiber, a hollow fiber, a porous shape, etc. These molded products of the (meth)acrylic resin composition can be produced, for example, by a process of thermally melting the (meth)acrylic resin particles, such as injection molding, extrusion molding, blow molding, etc., or by further subjecting the primary molded product to secondary molding (vacuum molding, compression molding, etc.). The shape of the (meth)acrylic resin particles is preferably, for example, a powder having a particle diameter of 1 μm to 1000 μm, a cylindrical or spherical pellet having a major axis of about 1 mm to 10 mm, or a mixture thereof.

[0119] The (meth)acrylic resin particles may be further molded into a film to form an optical film, such as a polarizer protective film, a retardation film, a viewing angle compensation film, a light diffusion film, a reflection film, an anti-reflection film, an anti-glare film, a brightness enhancement film, or a conductive film for a touch panel.

[0120] These optical films generally have a (meth)acrylic resin layer made of a (meth)acrylic resin composition and a primer layer provided on the surface of the (meth)acrylic resin layer, and the primer layer contains particles.

[0121] The primer layer is, for example, a layer made of at least one resin selected from a urethane resin, a cellulose resin, a polyol resin, a polycarboxylic acid resin, and a polyester resin.

[0122] The particles may be organic particles or inorganic particles. The organic particles are, for example, particles containing an organic polymer such as a (meth)acrylic polymer having a (meth)acrylic monomer as a constituent unit, or a styrene polymer having a styrene monomer as a constituent unit. The constituent units of the organic polymer (such as a (meth)acrylic monomer or a styrene monomer) may be prepared through recycling such as chemical recycling. The inorganic particles are, for example, silica particles, alumina particles, titania particles, zirconia particles, glass particles, etc. These particles may also be prepared through recycling.

[0123] The molding temperature of the (meth)acrylic resin composition is not particularly limited, but is preferably in the range of 150°C to 350°C, and more preferably in the range of 200°C to 300°C.

[0124] The (meth)acrylic resin composition of the present invention can reduce roll contamination, and furthermore, inhibits the occurrence of silver streaks and has excellent stability. Therefore, a molded article using the (meth)acrylic resin composition has excellent appearance and can be produced with high efficiency.

[0125] This application claims the benefit of priority based on Japanese Patent Application No. 2022-004679, filed on January 14, 2022. The entire contents of the specification of Japanese Patent Application No. 2022-004679, filed on January 14, 2022, are incorporated by reference into this application. EXAMPLES

[0126] The present invention will be described in more detail below with reference to experimental examples, but the present invention is not limited to the following experimental examples, and can be modified as appropriate within the scope of the above and below, and all of these modifications are within the technical scope of the present invention. In the following experimental examples, unless otherwise specified, "parts" means "parts by mass," "ppm" means "ppm by mass," and "%" means "% by mass."

[0127] First, the measurement methods employed in the following experimental examples will be described. (1) Weight average molecular weight, number average molecular weight, molecular weight distribution The weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution (Mw / Mn) of the (meth)acrylic resin in the polymerization solution and after polymerization were determined in terms of polystyrene using gel permeation chromatography (GPC). The apparatus and conditions used for the measurements are as follows: Measurement system: Tosoh GPC system HLC-8220 Measurement column configuration: Guard column (Tosoh, TSK guardcolumn SuperHZ-L) Separation columns (Tosoh, TSK Gel Super HZM-M), 2 columns connected in series Reference column configuration: Reference column (Tosoh, TSK gel SuperH-RC) Developing solvent: Chloroform (Wako Pure Chemical Industries, special grade) Flow rate of developing solvent: 0.6mL / min Standard sample: TSK standard polystyrene (Tosoh, PS-oligomer kit)

[0128] (2) Conversion rate The conversion rate (polymerization rate) (mass%) during the polymerization reaction was calculated from the formula (A) by measuring the unreacted monomer concentration (mass%) in the obtained polymerization solution using gas chromatography (manufactured by Shimadzu Corporation, apparatus name: GC17A). Conversion rate (polymerization rate) = 100 × (1-M1 / M0) ... (A) In the formula, M1 represents the unreacted monomer concentration (% by mass) in the polymerization solution, and M0 represents the monomer concentration (% by mass) in the charged raw material solution.

[0129] (3) Glass transition temperature The glass transition temperature (Tg) of the (meth)acrylic resin composition was determined by the starting point method in accordance with the provisions of JIS K7121. Specifically, a differential scanning calorimeter (Rigaku Corporation, Thermo plus EVO DSC-8230) was used to evaluate the Tg from a DSC curve obtained by heating about 10 mg of a sample from room temperature to 200° C. (heating rate 20° C. / min) under a nitrogen gas flow (100 ml / min). α-alumina was used as a reference.

[0130] (4) Lactone cyclization rate 2 parts of the (meth)acrylic resin composition was dissolved in 20 parts of chloroform, and the resulting solution was dropped into 200 parts of methanol to obtain a solution containing a precipitate. The solution containing the precipitate was filtered, and the precipitate was extracted and dried in a vacuum dryer at 80°C for 4 hours to obtain a sample. The obtained sample was analyzed by the following method (dynamic TG method), and the lactone cyclization rate (%) was calculated from formula (B). Measurement equipment: Differential thermobalance (Rigaku Corporation, ThermoPlus2 TG-8120, Dynamic TG) Measurement conditions: Sample amount 10 mg Heating rate: 10℃ / min Atmosphere: Nitrogen flow 400mL / min Method: Temperature increase using stepwise isothermal control method (mass loss rate controlled to 0.005% / sec or less within the range of 60℃ to 400℃) Lactone cyclization rate = 1 - (X / Y) ... (B) In formula (B), X represents the mass reduction rate (mass%) in the dealcoholization reaction from 150°C before the mass reduction starts to 300°C at which the polymer starts to decompose, and Y represents the theoretical mass reduction rate when it is assumed that all hydroxyl groups in the polymer composition are dealcoholized (lactone cyclization) (i.e., the weight reduction rate calculated on the assumption that 100% of the dealcoholization reactions that can occur in the polymer composition have occurred; mass%). For example, in the case of the polymers obtained in the examples and comparative examples, the molecular weight of methanol generated by the lactone cyclization reaction is 32, the molecular weight of methyl 2-(hydroxymethyl)acrylate is 116, and the composition ratio of the polymer before lactone cyclization is 12% by mass, so the theoretical mass reduction rate Y is (32 / 116)×12=3.31% by mass.

[0131] (5) Phosphorus atom content A sample solution in which 0.2 parts of the (meth)acrylic resin composition was dissolved in 99.8 parts of 2-butanone was used to measure the phosphorus atom content (ppm) in the (meth)acrylic resin composition using an ICP emission spectrometer (iCAP6500 Duo, manufactured by Thermo Fisher Scientific).

[0132] (6) Alcohol content measurement Sample preparation: 2 parts of the (meth)acrylic resin composition was dissolved in 20 parts of chloroform, and the obtained solution was dropped into 200 parts of methanol to obtain a solution containing a precipitate. The solution containing the precipitate was filtered, and the methanol-soluble components were extracted and dried to obtain a sample, which was then dissolved in acetone to obtain a sample solution. Measurement: The obtained sample solution was measured using GC-MS to identify the alcohol components detected other than methanol. Furthermore, the sample solution was measured using gas chromatography (Shimadzu Corporation, device name: GC17A) to quantify the content (ppm) of alcohol components other than methanol in the (meth)acrylic resin composition.

[0133] (7) Adhesion evaluation The (meth)acrylic resin composition was sandwiched between thin aluminum plates (manufactured by Nippon Test Panel, film thickness 0.1 mm), and then sandwiched between SUS plates on top of the thin aluminum plates, and melt-press molded for 5 minutes at 250°C using a manual heating press (manufactured by Imoto Machinery Co., Ltd., IMC-180C type). After that, it was removed from the press while still sandwiched between the SUS plates and cooled for 1 minute, and then when the thin aluminum plates were peeled off, if the resin composition was entirely attached to the thin aluminum plate, the adhesion was judged to be "good", if the resin composition was partially attached, the adhesion was judged to be "average", and if the thin aluminum plate could be peeled off without the resin composition adhering, the adhesion was judged to be "poor".

[0134] (8) Roll contamination evaluation For the (meth)acrylic resin composition, roll contamination was evaluated by open film formation. Specifically, the film was formed in the following manner. A melt film was produced using a vented single-screw extruder having a barrier flight type screw with a diameter of 65 mm and L / D=32. The temperatures of the cylinder and gear pump of the extruder were set to 275°C, and the temperatures of the polymer filter and T-die were set to 270°C. The pellets made of the (meth)acrylic resin composition were heated to 65°C by blowing heated dehumidified air into the hopper. In addition, a nitrogen inlet tube was provided at the bottom of the hopper to introduce nitrogen gas into the extruder. The pellets were melted by the single-screw while suctioning at 25 Torr from the vent port, and passed through a leaf disk type polymer filter with a filtration accuracy of 5 μm using a gear pump. Next, the molten resin was extruded from a T-die with a width of 600 mm and cast onto a hard chrome-plated cooling roll whose temperature was adjusted to 115°C, to obtain a raw film with a thickness of 145 μm. After the above melt film formation, the surface of the cast cooling roll was visually observed. If no turbidity was observed, the film was judged as "good." If turbidity was observed only at the ends in the width direction of the film, the film was judged as "average." If turbidity was observed also in the center in the width direction of the film, the film was judged as "poor."

[0135] (9) Foamability evaluation The (meth)acrylic resin composition was dried in a vacuum dryer at 100°C for 4 hours, filled into a cylinder specified in JIS-K7210, and held at 280°C, the temperature assumed for molding, for 20 minutes, and then extruded into a strand, and the presence or absence of silver streaks between the upper and lower marks of the resulting strand was visually confirmed. Cases where silver streaks were observed were marked with "X", and cases where they were not observed were marked with "O".

[0136] Example 1 In a reaction vessel equipped with a stirrer, a temperature sensor, a cooling condenser, and a nitrogen inlet tube, 83.5 parts of methyl methacrylate (MMA), 12 parts of 2-(hydroxymethyl)methyl acrylate (MHMA; also called α-(hydroxymethyl)methyl acrylate), and 88.7 parts of toluene were charged, and the temperature was raised to 105°C while nitrogen was passed through the reaction vessel. When refluxing began with the temperature rise, 0.535 parts of a 20% by weight toluene solution of t-amyl peroxy isononanoate (manufactured by Arkema Yoshitomi Co., Ltd., Luperox (registered trademark) 570T20) was added as a polymerization initiator. Subsequently, a solution consisting of 4.5 parts of styrene (St) and 0.15 parts of n-dodecyl mercaptan (nDM) was added dropwise over 2 hours. In addition, 1.065 parts of a 20% by weight toluene solution of t-amyl peroxy isononanoate was added dropwise over 4 hours. During the dropwise addition of St, nDM, and t-amyl peroxyisonanoate, the mixture was refluxed at about 105 to 110°C to allow solution polymerization to proceed. After the dropwise addition was completed, the mixture was aged for an additional 2 hours at the same temperature. When the polymerization was completed (6 hours after the start of polymerization), a portion of the polymerization solution was extracted and evaluated for molecular weight (Mw) and conversion rate, which were 157,000 and 91.3% by mass, respectively.

[0137] Next, 0.0312 parts of butyl phosphate (Phoslex A-4, manufactured by SC Organic Chemical Co., Ltd.) was added as a catalyst (cyclization catalyst) for the cyclization condensation reaction to the obtained polymerization solution, and the cyclization condensation reaction for forming a lactone ring structure was allowed to proceed for 2 hours under reflux at about 90 to 110° C. Furthermore, the obtained polymerization solution was passed through a multi-tube heat exchanger heated to 235° C. to complete the cyclization condensation reaction.

[0138] Thereafter, the obtained polymerization solution was introduced into a vent-type twin-screw extruder (L / D=52.5) ​​at a processing speed of 100 parts / hour in terms of resin amount, and devolatilization treatment was performed. The extruder was equipped with one rear vent, four fore vents (hereinafter referred to as the first, second, third, and fourth vents from the upstream side), and a side feeder between the third and fourth vents, and the rotation speed was 80 rpm, the vacuum degree was 25 to 800 hPa, and the barrel temperature was 255 ° C (heated with a heat medium at 255 ° C). In addition, the extruder was equipped with a leaf disk-type polymer filter (filtration accuracy 10 μm) at the tip, and the extrusion die provided at the tip of the polymer filter had a large number of fine holes formed along the circumference of the resin discharge surface, and a cutter of a watering cut type was attached. In addition, after cutting and water-cooling solidification, a dehydration facility using a centrifugal dryer was provided, and the composition was such that it was transported to a storage silo by gas transport. When the polymerization solution was introduced, ion-exchanged water was introduced at a rate of 1.5 parts / hour from the upstream of the second and third vents, and ion-exchanged water was introduced at a rate of 3 parts / hour from the upstream of the fourth vent. After the devolatilization was completed, the mixture was passed through a leaf disk-type polymer filter (filtration accuracy: 10 μm), and then the molten (meth)acrylic resin composition was extruded from the die (pores) of the extrusion die, cut, cooled and solidified with water, dehydrated with a centrifugal dryer, transported, and cooled in a storage silo to obtain a (meth)acrylic resin composition (A-1). The composition of the obtained (meth)acrylic resin composition (A-1) is shown in Table 1, and its physical properties are shown in Table 2.

[0139] Example 2 A (meth)acrylic resin composition (A-2) was obtained in the same manner as in Example 1, except that 0.0468 parts of butyl phosphate (Phoslex A-4, manufactured by SC Organic Chemical Co., Ltd.) was added as a catalyst for the cyclization condensation reaction (cyclization catalyst). The composition of the obtained (meth)acrylic resin composition (A-2) is shown in Table 1, and each physical property is shown in Table 2.

[0140] Example 3 A (meth)acrylic resin composition (A-3) was obtained in the same manner as in Example 1, except that 0.0624 parts of butyl phosphate (Phoslex A-4, manufactured by SC Organic Chemical Co., Ltd.) was added as a catalyst for the cyclization condensation reaction (cyclization catalyst). The composition of the obtained (meth)acrylic resin composition (A-3) is shown in Table 1, and each physical property is shown in Table 2.

[0141] Example 4 After completing the cyclization condensation reaction in the same manner as in Example 2, a vent-type screw twin-screw extruder (L / D=52.5) ​​was used to carry out a devolatilization treatment. The same procedure was followed as in Example 2, except that a toluene solution containing 35% by mass of an ultraviolet absorber (ADEKA CORPORATION, Adeka STAB (registered trademark) LA-F70) was added from the upstream of the third vent at a rate of 1.92 parts / hour, to obtain a (meth)acrylic resin composition (A-4). The compounding composition of the obtained (meth)acrylic resin composition (A-4) is shown in Table 1, and the physical properties are shown in Table 2.

[0142] Example 5 A (meth)acrylic resin composition (A-5) was obtained in the same manner as in Example 1, except that 0.0475 parts of octyl phosphate (Phoslex A-8N, manufactured by SC Organic Chemical Co., Ltd.) was added as a catalyst for the cyclization condensation reaction (cyclization catalyst). The blending composition of the obtained (meth)acrylic resin (A-5) composition is shown in Table 1, and each physical property is shown in Table 2.

[0143] Comparative Example 1 In a reaction vessel equipped with a stirrer, a temperature sensor, a cooling condenser, and a nitrogen inlet tube, 83.5 parts of MMA, 12 parts of MHMA, 0.07 parts of nDM, and 88.7 parts of toluene were charged, and the temperature was raised to 105°C while nitrogen was passed through the reaction vessel. When refluxing with the temperature increase began, 0.451 parts of a 20% by weight toluene solution of t-amyl peroxy isononanoate (manufactured by Arkema Yoshitomi Co., Ltd., Luperox (registered trademark) 570T20) was added as a polymerization initiator. Subsequently, a solution consisting of 4.5 parts of St and 0.899 parts of a 20% by weight toluene solution of t-amyl peroxy isononanoate was dropped over 2 hours. While St and t-amyl peroxy isonanoate were dropped, the mixture was refluxed at about 105 to 110°C to allow solution polymerization to proceed. After the dropwise addition, the mixture was aged for another 4 hours at the same temperature. When the polymerization was completed (6 hours after the start of polymerization), a part of the polymerization solution was sampled and evaluated for molecular weight (Mw) and conversion rate, which were 153,000 and 94.5% by mass, respectively.

[0144] Next, 0.075 parts of stearyl phosphate (Phoslex A-18, manufactured by SC Organic Chemical Co., Ltd.) was added to the obtained polymerization solution as a catalyst (cyclization catalyst) for the cyclization condensation reaction, and the cyclization condensation reaction for forming a lactone ring structure was allowed to proceed for 2 hours under reflux at about 90 to 110° C. Furthermore, the obtained polymerization solution was passed through a multi-tube heat exchanger heated to 235° C. to complete the cyclization condensation reaction.

[0145] Thereafter, the obtained polymerization solution was introduced at a processing rate of 100 parts / hour in terms of the amount of resin using the vent-type screw twin-screw extruder (L / D=52.5) ​​used in Example 1, and devolatilization treatment was performed. When introducing the polymerization solution, ion-exchanged water was introduced at a rate of 1.5 parts / hour from the upstream of the second and fourth vents, and a toluene solution consisting of a zinc octylate toluene solution (Nihon Kagaku Sangyo Co., Ltd., Nikka Octix Zinc 1.8%):phenol-based antioxidant (ADEKA Corporation, Adeka STAB (registered trademark) AO-60):sulfur-based antioxidant (ADEKA Corporation, Adeka STAB (registered trademark) AO-412S) = 33.74:1:1 was introduced at a rate of 0.165 parts / hour from the upstream of the third vent. After the devolatilization, the mixture was passed through a leaf disk-type polymer filter (filtration accuracy: 5 μm), and then the molten (meth)acrylic resin composition was extruded from the die (pores) of the extrusion die, cut, solidified by cooling with water, dehydrated by a centrifugal dryer, transported, and cooled in a storage silo to obtain a (meth)acrylic resin composition (A-6). The composition of the obtained (meth)acrylic resin (A-6) composition is shown in Table 1, and its physical properties are shown in Table 2.

[0146] Comparative Example 2 A (meth)acrylic resin composition (A-7) was obtained in the same manner as in Example 1, except that 0.1 parts of methyl phosphate (Phoslex A-1, manufactured by SC Organic Chemical Co., Ltd.) was added as a catalyst for the cyclization condensation reaction (cyclization catalyst). The blending composition of the obtained (meth)acrylic resin (A-7) composition is shown in Table 1, and each physical property is shown in Table 2.

[0147] [Table 1]

[0148] [Table 2]

[0149] As is clear from Table 2, the (meth)acrylic resin compositions (A-1) to (A-5) obtained in Examples 1 to 5 all had good adhesion evaluations, while the (meth)acrylic resin composition (A-6) obtained in Comparative Example 1 had a poor adhesion evaluation. In particular, the (meth)acrylic resin compositions (A-1) to (A-4) obtained using butyl phosphate showed excellent results in terms of adhesion.

[0150] As is clear from Table 2, the (meth)acrylic resin compositions (A-1) to (A-5) obtained in Examples 1 to 5 all had good evaluations for roll contamination, while the (meth)acrylic resin composition (A-6) obtained in Comparative Example 1 had a bad evaluation for roll contamination. In particular, the (meth)acrylic resin compositions (A-1) to (A-4) obtained using butyl phosphate showed excellent results for roll contamination.

[0151] As is clear from Table 2, the (meth)acrylic resin compositions (A-1) to (A-5) obtained in Examples 1 to 5 all had good evaluations for foamability, while the (meth)acrylic resin composition (A-7) obtained in Comparative Example 2 had a poor evaluation for foamability.

Claims

1. A (meth)acrylic resin composition comprising a (meth)acrylic polymer having a ring structure, which is at least one of a lactone ring structure and a glutaric anhydride structure, in a main chain, the (meth)acrylic polymer having a ring structure has a structural unit derived from a (meth)acrylic monomer and a structural unit derived from a styrene monomer, The content of phosphorus atoms in the (meth)acrylic resin composition is 1.0 ppm or more and 50 ppm or less, A (meth)acrylic resin composition, characterized in that when the content of a compound represented by the following formula (I) in the (meth)acrylic resin composition is measured by the following alcohol component measurement, the compound represented by the formula (I) is not detected. 【Chemistry 1】 [In formula (I), R 1 represents an aliphatic hydrocarbon group having 13 or more carbon atoms, or an aromatic hydrocarbon group having 6 or more carbon atoms. <Alcohol content measurement> 2 parts by mass of the (meth)acrylic resin composition is dissolved in 20 parts by mass of chloroform, the resulting solution is dropped into 200 parts by mass of methanol to obtain a solution containing a precipitate, the solution is filtered, and the filtrate obtained is dried to obtain a sample. The sample is dissolved in acetone to obtain a sample solution. The sample solution is measured using GC-MS to identify and quantify the amount of alcohol components detected other than methanol.

2. 2. The (meth)acrylic resin composition according to claim 1, wherein the content of the compound represented by the following formula (II) in the (meth)acrylic resin composition is 95 ppm or less: 【Chemistry 2】 [In formula (II), R 2 represents an aliphatic hydrocarbon group having 3 to 12 carbon atoms.

3. The (meth)acrylic resin composition according to claim 1, wherein the content of the ring structural unit in the (meth)acrylic polymer having a ring structure is from 5% by mass to 70% by mass.

4. 2. The (meth)acrylic resin composition according to claim 1, wherein the content of the (meth)acrylic polymer having a ring structure in the (meth)acrylic resin composition is 50% by mass or more.

5. The (meth)acrylic resin composition according to claim 1, which has a glass transition temperature of 120° C. or higher.

6. The (meth)acrylic resin composition according to claim 1 , which does not contain a hindered phenol compound.

7. The (meth)acrylic resin composition according to claim 1 , which does not contain an organophosphorus compound having a hindered phenol moiety.

8. A molded article comprising the (meth)acrylic resin composition according to any one of claims 1 to 7.

9. The molded article according to claim 8, which is in the form of a sheet, a film or a lens.

10. A method for producing a (meth)acrylic resin composition, comprising a cyclization step of carrying out at least one of the following cyclization reactions (i) and (ii) in a (meth)acrylic polymer to form a ring structure in a main chain of the (meth)acrylic polymer, (i) A cyclization reaction between a hydroxy group and an ester group or a carboxyl group to form a lactone ring structure. (ii) A cyclization reaction between a carboxyl group and an ester group or another carboxyl group to form a glutaric anhydride structure. In the cyclization reaction, at least one selected from the group consisting of C3-7 alkyl phosphate, C3-7 alkyl phosphite, and C3-7 alkyl hypophosphite is used as a catalyst; A method for producing a (meth)acrylic resin composition, characterized in that the amount of the catalyst used is 100 ppm or more and 700 ppm or less, calculated by mass, based on the total amount of monomer components constituting the (meth)acrylic polymer.

11. The method for producing a (meth)acrylic resin composition according to claim 10, wherein the catalyst used in the cyclization reaction is at least one selected from the group consisting of butyl phosphate, butyl phosphite, and butyl hypophosphite.

12. The method for producing a (meth)acrylic resin composition according to claim 10, wherein the catalyst has a decomposition temperature of 160° C. or higher.

13. The method for producing a (meth)acrylic resin composition according to any one of claims 10 to 12, further comprising a polymerization step of polymerizing a (meth)acrylic monomer to form the (meth)acrylic polymer.

14. The method for producing a (meth)acrylic resin composition according to claim 13, wherein a total content of structural units derived from the (meth)acrylic monomer in all structural units of the (meth)acrylic polymer is 50 mass% or more.

15. The method for producing a (meth)acrylic resin composition according to claim 13, wherein the (meth)acrylic monomer comprises an α-(1-hydroxyalkyl)alkyl acrylate, and the total content of structural units derived from the α-(1-hydroxyalkyl)alkyl acrylate in all structural units of the (meth)acrylic polymer is 5 mass% or more.

16. an additive is added in one or more steps selected from the polymerization step, the cyclization step, and a step subsequent to the cyclization step; The method for producing a (meth)acrylic resin composition according to claim 13, wherein the additive does not include a hindered phenol compound or an organophosphorus compound having a hindered phenol moiety.

Citation Information

Patent Citations

  • Method of manufacturing for transparent heat resistant resin and use of the same

    JP2001151814A

  • Stretched film and production method thereof

    JP2014069437A

  • Methacrylic resin composition

    JP2017145387A

  • Process for production of alkene having hydroxyl group, and alkene having hydroxyl group

    WO2007123253A1